NUT Midline Carcinoma in Elderly Patients: Usefulness of 18F-FDG PET/CT for Treatment Assessment. (September 2015) - Kawase, Takatsugu; Naka, Go; Kubota, Kazuo; Sakashita, Baku; Takeda, Yuichiro
Abstract : Abstract: Nuclear protein in testis (NUT) midline carcinoma is a rare disease that generally arises in adolescents and young adults. However, we encountered a rare NUT midline carcinoma case in an elderly patient. 18 F-2-fluoro-2-deoxyglucose positron emission tomography/computed tomography (PET/CT) studies were performed before and during the treatment course. In this case, the initial PET/CT study revealed locoregional hypermetabolism in the mediastinal lesion. After then, the interim PET/CT study indicated a clear diminishing response to the initial treatment, whereas the residual masses were morphologically observable. Nuclear imaging may allow visualization of the therapeutic effect of antineoplastic therapies in both young and elderly patients.